THE INFLUENCE OF GIVING LIME (Citrus Aurantifolia) WITH FE TABLETS TO INCREASE HEMOGLOBIN LEVELS AMONG THE THIRD TRIMESTER OF ANEMIA PREGNANT WOMEN - Rahmawati, Eva Silviana; Cholilla, Nur; Nuraini, Nanik; Susanti, Retno (UNIVERSITAS AIRLANGGA, 2023)
Background: Problems caused by anemia in pregnancy range from mild complaints to severe complications. To prevent anemia, every pregnant woman is expected to get iron tablets at least 90 tablets during pregnancy to increase hemoglobin. Lime contains high levels of vitamin C, vitamin C helps iron absorption by up to 30%. The purpose of the study was to determine the effect of providing lime juice assistance along with Fe tablets to increasing hemoglobin levels in pregnant women with anemia in the third trimester. Method: The study design was a pre-post control group design. The population in this study were all 36 pregnant women with anemia in the third trimester at the Soko Community Health Center, using random sampling technique. The sample size is 32 respondens divided into two group. The treatment group given Fe tablets and lime for 14 days, and statistical analysis using Wilcoxon test. Result: The results of the study using SPSS for windows with a significance level of α = 0.005 obtained a value of p = 0.04 which was proven to be 0.031 <0.05, so H1 is accepted meaning there is an influence. Conclusion : There is an effect of providing lime juice accompaniment along with Fe tablets on increasing hemoglobin levels in pregnant women with anemia in the third trimester. For future researchers, this research can continue to be developed to create a product of economic value that can be utilized by the community